2021
DOI: 10.4018/joeuc.286808
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Motivation and Self-Disclosure Intention

Abstract: Studies that specifically discuss the formation of autonomous motivations of users of social networking services (SNSs) and how such motivation influences SNS user intention to disclose personal location-related information (PLRI) are absent from the literature. Consequently, this study, based on the self-determination theory and the information system success (ISS) model, investigates the relationships among key system-related quality factors, SNS users’ autonomous motivations and user satisfaction regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Fifth, our study responds to calls from Wang et al (2021) and Li and Zhu (2022), who studied the influence of system quality on user satisfaction, among other variables, and proposed future lines of research to extend their analysis to different contexts. Furthermore, our findings regarding the determinants of perceived usefulness for processes reinforce those obtained for other information systems (Alkhawaja et al , 2022; Fauzi et al , 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Fifth, our study responds to calls from Wang et al (2021) and Li and Zhu (2022), who studied the influence of system quality on user satisfaction, among other variables, and proposed future lines of research to extend their analysis to different contexts. Furthermore, our findings regarding the determinants of perceived usefulness for processes reinforce those obtained for other information systems (Alkhawaja et al , 2022; Fauzi et al , 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Certain scholars analyzed the influencing factors of social media user privacy disclosure willingness and behavior from different perspectives. Wang et al conducted research from the perspective of information systems and concluded that the system quality, service quality, and information quality of social networking sites have a positive impact on user willingness to disclose personal location-related information (PLRI) [27]. From the perspective of sociology, Lin et al, Liu et al, and other scholars analyzed the privacy disclosure willingness of social networking site users with social exchange theory and trust theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Option Pricing Model 2 Wireless Communications and Mobile Computing combined with computer simulation technology, on the one hand, the advantages of stock options can be exerted, and on the other hand, the unstable changes of direct assets and the risks of market currency transactions can be avoided, allowing participants to complete transactions more smoothly. Due to the nonstorable characteristics of financial items, the system dispatch center must strictly control the transaction plan and repeatedly verify the security of the financial option pricing model system [15][16][17]. This requires a large amount of information exchange between the participants and the option pricing model, which increases the accuracy of option pricing to a certain extent and avoids risks [18].…”
Section: Computer Simulation On the Financialmentioning
confidence: 99%